Job relatedness, local skill coherence and economic performance: a job postings approach - Martin Henning; Rikard Eriksson; Petrus Garefelt; Hanna Martin; Zoltán Elekes (Regional Studies, Regional Science)
The local presence and composition of skills is commonly thought to have enormous implications for economic development. Yet, skills and the relations between them are notoriously difficult to pinpoint and measure. We develop a method that uses information available in Swedish job postings to measure the skill-relatedness of jobs and the skill-coherence of local economies. Our skill-relatedness measure can be assumed to be exogenous to local economic outcomes such as wages, productivity and labour mobility. We corroborate some previous research findings and show that workers tend to switch between related jobs and that local economies are on average skill-coherent. However, less coherent local economies are associated with higher average wages and productivity. Local economies where workers switch between related jobs though enjoy higher average wages. In all, this points to the benefit of local labour market clusters within more diverse regions. We conclude that job postings provide a wealth of information on the skill-foundations of local development. A job-level skill-relatedness matrix accompanies the paper.